PERANCANGAN KUNCI PINTU OTOMATIS MENGGUNAKAN SENSOR RFID BERBASIS ARDUINO NANO DENGAN IOT WEB API (Jurnal Informatika dan Komputasi: Media Bahasan, Analisa dan Aplikasi, 2024)
Abstract Very rapidly technological advances allow for various efforts to provide convenience and comfort forhumans, one of which is to make everything completely automated. Automatic door locks using RFIDsensors based on Arduino Nano are door locks that open automatically by attaching a card to an RFIDsensor (Radio frequency identification) as the input media. Automatic door locks have been widely usedin daily life, however, in making automatic door locks require a large cost. In this thesis the authormakes the design of a simple automatic door lock, this automatic door lock works by utilizing theArduino nano microcontroller as a control system, RFID sensors as input media, solenoid as a keydrive system and WEB API as a media user interface. The existence of this automatic door lock willprovide benefits in human life, because it can facilitate the owner in maintaining the security of theirhome.